STUDENTS' MATHEMATICAL THINKING SKILL VIEWED FROM CURIOSITY THROUGH PROBLEM-BASED LEARNING MODEL ON INTEGRAL CALCULUS - Zetriuslita Zetriuslita; Rezi Ariawan (IKIP Siliwangi and I-MES, 2021)
This study aims to find out the improvement of students’ mathematical critical thinking viewed from curiosity through teaching materials with Problem Based Learning model. This is quasi-experimental research. The samples are, where the overall population consists of 75 samples divided into two classes. This research employed a simple random sampling technique. The instruments were the mathematical critical thinking skill test and curiosity questionnaire. The technique of data collection was carried out with test and non-test techniques. The data were analyzed through a two-way Anova test. Based on the analysis and interpretation of the research findings, it was found that: there was an improvement in students’ mathematical critical thinking skill from High curiosity by using teaching materials with Problem Based Learning model; 1) There was an improvement from Average curiosity through learning with Integral Calculus teaching materials; 2) There was an improvement from Low curiosity; 3) There was no improvement from the level of curiosity (High, Medium, Low) through Problem-based Learning. 4) There was no influence between the level of curiosity and learning in improving students’ mathematical critical thinking skills. Do more in-depth studies related to improving mathematical critical thinking skills by reviewing other affective aspects.